2014
DOI: 10.2174/1568026614666140324142409
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alkaloids and Semisynthetic Indole Derivatives as Multifunctional Scaffolds Aiming the Inhibition of Enzymes Related to Neurodegenerative Diseases – A Focus on Psychotria L. Genus

Abstract: Indole alkaloids and synthetic indole derivatives are well known for their therapeutic importance. In fact, preclinical and clinical studies had already demonstrated several pharmacological activities for these compounds. Here, we overview the multifunctional potential of these molecules for the inhibition of enzymes related to neurodegenerative disease: acetylcholinesterase (AChE), butyrylcholinesterase (BChE), monoamine oxidases A and B (MAO-A and MAO-B). A focus will be given on Psychotria L. genus, conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Indole alkaloids are marine natural products that show specific biological activities, such as anti-inflammatory and serotonin antagonism [ 41 ]. Moreover, the therapeutic importance of this kind of indole scaffolds is well known, as demonstrated by clinical and preclinical studies showing pharmacological activities over neurodegenerative diseases, such as AD [ 41 , 50 ]. Within the group of compounds containing the indole moiety are meridianins, for instance.…”
Section: Resultsmentioning
confidence: 99%
“…Indole alkaloids are marine natural products that show specific biological activities, such as anti-inflammatory and serotonin antagonism [ 41 ]. Moreover, the therapeutic importance of this kind of indole scaffolds is well known, as demonstrated by clinical and preclinical studies showing pharmacological activities over neurodegenerative diseases, such as AD [ 41 , 50 ]. Within the group of compounds containing the indole moiety are meridianins, for instance.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the potential therapeutic effects of halogenated indoles, indole alkaloids, and semisynthetic indole derivatives have attracted considerable research interest 3537 . For example, halogen substituted indoles have been shown to eliminate Escherichia coli and Staphylococcus aureus persister cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…AChE existence majorly contributes in the pathogenesis of AD which is more often associated with the formation of neurofibrillary tangles and Aβ plaques 147 . Harmine has been reported to target the pathogenesis of AD because of its efficacy to potentially penetrate the BBB, the parenchyma cells of brain as well as constrain the activity of AChE 193 which is the key enzyme involved in the metabolism and breakdown of a neurotransmitter known as ACh 194 . An experimental study suggested that harmine at the dose of 20 mg/kg could efficiently augment spatial cognition as well as amend compromised memory via cholinergic neurotransmission improvement 193 .…”
Section: Harminementioning
confidence: 99%
“…Harmine has been reported to target the pathogenesis of AD because of its efficacy to potentially penetrate the BBB, the parenchyma cells of brain as well as constrain the activity of AChE 193 which is the key enzyme involved in the metabolism and breakdown of a neurotransmitter known as ACh 194 . An experimental study suggested that harmine at the dose of 20 mg/kg could efficiently augment spatial cognition as well as amend compromised memory via cholinergic neurotransmission improvement 193 . Another pathological feature in AD is the aggregation and accumulation of tau proteins as well as the overexpression of brain proliferative agent named as tyrosine-phosphorylation regulated kinase (DYRK1A) 195 .…”
Section: Harminementioning
confidence: 99%